Health Promotion To Improve Public Health About Covid-19 Through Interactive Education For Surya Nusantara College Students And Academy Students Of Sma Swasta Advent In Pematangsiantar - Rosnancy Renolita Sinaga; Sedia Simbolon; Donald Loffie Muntu (Universitas Malahayati Lampung, 2022)
ABSTRACT In the beginning year of 2020, the World Health Organization (WHO) declared the coronavirus outbreak as a Global Public Health Emergency. Coronavirus is continuing its spread across the world. The virus is surging in many regions and countries that had apparent success in suppressing initial outbreaks are also seeing infections rise. The COVID-19 pandemic has led to a dramatic loss of human life worldwide and presents an unprecedented challenge to public health, food systems and the world of work. The impact of the COVID-19 pandemic was now beginning to spread to the world of education. The policies taken by many countries including Indonesia by dismissing all educational activities and related institutions must present alternative educational processes for students and students who cannot carry out the educational process in educational institutions. This community project was aimed to increase the knowledge of COVID-19 and to promote the health status of college students in Surya Nusantara Nursing School, School of Business, School of Theology and academy students as well. These schools are situated in the area of Pondok Sayur, city of Pematangsiantar. It is expected that those who completed the health promotion seminar would be able to conduct effective prevention and control activities for COVID-19 as per the guidelines in primary health centers across the country. The main aim of this community project was to encourage behaviour change among the people that will help them adapt helpful behaviours in the long fight against COVID-19.Keywords: Covid-19, Health Promotion, Interactive Education, Students